2021
DOI: 10.3390/life11111267
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy Presents Similar Symptoms and Pathological Changes in Both High-Fat Diet and Pharmacologically Induced Pre- and Diabetic Mouse Models

Abstract: The objective of the study was to compare the effects of experimentally induced type 1 or type 2 diabetes (T1D or T2D) on the functional, structural and biochemical properties of mouse peripheral nerves. Eight-week-old C57BL/6 mice were randomly assigned into three groups, including the control (CTRL, chow-fed), STZ (streptozotocin (STZ)-injected), and HFD (high-fat diet (HFD)-fed) group. After 18-weeks of experimental treatment, HFD mice had higher body weights and elevated levels of plasma lipids, while STZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 39 publications
1
28
2
Order By: Relevance
“…Previous studies indicate nondiabetic rodents fed a high fat diet develop obesity (Obrosova et al, 2007;Watcho et al, 2010;Jaroslawska et al, 2021), dyslipidemia (Vincent et al, 2009;Guilford et al, 2011;Ozay et al, 2014;Zhang et al, 2018;Jaroslawska et al, 2021), and signs of PN including morphological changes in peripheral nerves (Zhang et al, 2018), reduced sensory and motor nerve conduction velocities (Vincent et al, 2009;Xu et al, 2014), altered thermal sensitivity (Obrosova et al, 2007;Guilford et al, 2011;Xu et al, 2014;Zhang et al, 2018), and mechanical hypersensitivity (Guilford et al, 2011;Xie et al, 2013;Zhang et al, 2018). However, the distinct mechanisms underlying high fat diet-induced PN have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate nondiabetic rodents fed a high fat diet develop obesity (Obrosova et al, 2007;Watcho et al, 2010;Jaroslawska et al, 2021), dyslipidemia (Vincent et al, 2009;Guilford et al, 2011;Ozay et al, 2014;Zhang et al, 2018;Jaroslawska et al, 2021), and signs of PN including morphological changes in peripheral nerves (Zhang et al, 2018), reduced sensory and motor nerve conduction velocities (Vincent et al, 2009;Xu et al, 2014), altered thermal sensitivity (Obrosova et al, 2007;Guilford et al, 2011;Xu et al, 2014;Zhang et al, 2018), and mechanical hypersensitivity (Guilford et al, 2011;Xie et al, 2013;Zhang et al, 2018). However, the distinct mechanisms underlying high fat diet-induced PN have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the vasa nervorum, which supply various nerve fibers, such as C-type and delta fibers responsible for specific functions of the nervous system, is mainly responsible for impaired wound healing in DM and its recurrence, especially in DFS [ 26 ]. This highlights the importance of imitating neuropathic changes in the design of the animal model [ 27 ]. Impaired microcirculation in the skin in patients with DM occurs due to damage to the vasa nervorum caused by thickening of the basal membrane of those arteries and their persistent occlusion by microclots.…”
Section: Molecular Pathways Of the Development Of Chronic Wounds In Dmmentioning
confidence: 99%
“…Until now, evidence indicated that a variety of factors, such as local neuroinflammation, malfunctions in cytoskeleton remodeling, impaired axonal transport, and enhanced oxidative stress, might be involved in the progression of LDN in patients suffering from diabetes. [6][7][8][9][10][11] Advanced glycation end products (AGEs) are the products of nonenzymatic glycation and oxidation of proteins and lipids. AGEs may accumulate in different biological locations, such as the peripheral nervous system (PNS).…”
Section: Introductionmentioning
confidence: 99%